Assessment of radiation exposure and safety practice in CT unit in a general hospital - Alsharif, Ali (Journal of King Abdulaziz University: Engineering Sciences, 2024)
As medical imaging technology in CT scanners improves to provide an accurate and safe diagnosis, the potential hazards of ionizing radiation remain a significant issue in daily medical practice for patients and medical staff. To reduce excessive radiation exposure, computed tomography (CT) parameters must be optimized. By utilizing a dose length product (DLP), this study aims to determine the diagnostic reference level (DRL) for CT in Jazan. Data sheets were sent to all three hospitals in the Jazan area that have CT scanners, and 300 patients were collected. From July 2022 to November 2022, data were collected for all patients undergoing CT CAP (Chest, Abdomen, and Pelvis). The DRL for CT CAP with contrast in venous phase examination was 981.9 mGy.cm in the Jazan area of the southern region of Saudi Arabia in 2023. Vast heterogeneity in radiation doses across hospitals suggests the need for the implementation of a national diagnostic reference level (NDRL) in Saudi Arabia. A phantom study experiment that was successful in this scientific paper helped to explain the optimization strategies in the CT unit. The dose report result was comparable with the three sections of the phantom experiment in that the high image quality at even lower radiation exposure was also achieved by the dose reduction methods employed in the CT phantom study experiment parameters such as tube voltage (kV), tube currents (mA), detector coverage (mm), helical thickness (mm), table pitch (mm/rot), and rotation time (s or sec). The phantom study experiment concluded that high image quality at very low dose levels can be achieved using a 100 kV and 120 kV protocol with 300 mA for head CT scans. An online survey was done to assess radiation exposure and safety practice awareness among hospital medical staff to establish the level of awareness among healthcare professionals in the Jazan area. The results of the online survey showed a lack of knowledge regarding radiation exposure, safety practices, and the precise amount of radiation in each imaging procedure. It is recommended to implement educational programs and comprehensive training to increase awareness of radiation protection knowledge.